The economy today - Schiller, Bradley R. 1943- (McGraw-Hill/Irwin, 2013)
Emphasizes how policymakers must choose between government intervention and market reliance to resolve the core issues of what, how, and for whom to produce. This title highlights this strategic choice throughout the range of micro, macro, and international issues